Development of a microprocessor-based biochemical sampler - Randhawa, S. S. (Hindawi Publishing Corporation, 2002)
Modern medicine requires patients to be treated on the basis of precise data, which are often obtained from electronic equipment. An inexpensive and portable microprocessor-based sampler developed by the authors is described. It is comprised of the following units: sample plate assembly, probe-drive linkage system, wash fluid receptacle, timing system and 8085A microprocessor.